Plasma Citrulline in the Diagnosis and Follow-Up of Celiac Disease - Alicia Isabel Pascual Pérez; Elene Larrea Tamayo; Santiago Jiménez Treviño; David González Jiménez; David Pérez Solís; Cristina Molinos Norniella; Juan José Díaz Martín (Children)
Background/Objectives: Citrulline, an amino acid produced by small bowel enterocytes, has been proposed as a potential marker of intestinal absorptive capacity. The aim of this study is to evaluate whether measuring citrulline levels could be useful for celiac disease (CD) patients, both at the time of diagnosis and during follow-up. Methods: A multicenter prospective study was conducted. Citrulline levels were measured and compared in 93 pediatric patients classified into three groups. Group A: 28 patients with newly diagnosed CD. In this group, an additional measurement was performed after 3–6 months on a gluten-free diet (GFD). Group B: 32 patients with a prior CD diagnosis and on a GFD for at least 6 months. Group C: 33 healthy controls. Citrulline levels were correlated with clinical and laboratory variables, including serological markers. Statistical analysis: t-tests for paired groups and independent groups, Pearson and Spearman correlation tests. Results: Newly diagnosed CD patients had lower citrulline levels compared to those on a GFD for more than 6 months (27.13 vs. 32.42 µmol/L; p > 0.05). Citrulline levels were nearly identical between healthy controls and CD patients on a GFD for more than 6 months (32.48 vs. 32.42 µmol/L; p > 0.05). Starting a GFD led to a significant increase in citrulline levels in group A (from 27.13 to 37.43 µmol/L, p < 0.001). Conclusions: Plasma citrulline could serve as a valuable marker for mucosal recovery in the follow-up of diagnosed celiac patients adhering to a GFD.